A technique for administering xenon gas anesthesia during surgical procedures in mice - Ruder, Arne Mathias; Schmidt, Michaela; Ludiro, Alessia; Riva, Marco A.; Gass, Peter (Lab animal, 2014)
Carrying out invasive procedures in animals requires the administration of anesthesia. Xenon gas offers advantages as an anesthetic agent compared with other agents, such as its protection of the brain and heart from hypoxia-induced damage. The high cost of xenon gas has limited its use as an anesthetic in animal experiments, however. The authors designed and constructed simple boxes for the induction and maintenance of xenon gas and isoflurane anesthesia in small rodents in order to minimize the amount of xenon gas that is wasted. While using their anesthesia delivery system to anesthetize pregnant mice undergoing caesarean sections, they measured the respiratory rates of the anesthetized mice, the survival of the pups and the percentages of oxygen and carbon dioxide within the system to confirm the system's safety.
Gesehen am: 02.06.2015